Analysis of Job Safety and Work Loyalty toward Work Readiness - Kurniawan, Ahmad (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
Characteristics of a soldier's work is quite heavy, so it demands physical, intellectual, and mental endurance. This gives a signal that the success of the soldiers' tasks depends on these three forces, so special attention is needed from stakeholders within the Indonesian military. In fact, this research was conducted to test the work readiness of soldiers who are influenced by factors such as work safety and loyalty to the state. This study uses a numerical data-based quantitative research structure as a basis for building arguments. The test tool to measure research results uses a regression test which consists of a partial test, simultaneous test, and determinant test. A total of 200 soldiers were asked for their willingness to be respondents using the incidental sampling technique. This research was conducted at the Indonesian military agency, namely the 4th Infantry Battalion based in Jakarta. The results of the study stated that the patriotic and professional attitude of soldiers would grow by 66% if they received assurance of life safety and a patriotic spirit. In addition, the role of self-readiness of soldiers is the key to achieving task success. This emphasizes the importance of building the readiness of the soldiers to work, so that the spirit of patriotism grows. However, managerial ranks need to provide support for occupational health and safety, as well as motivate soldiers to love their homeland.